Pengaruh Pendidikan Kesehatan Bantuan Hidup Dasar Terhadap Peningkatan Pengetahuan Siswa/I SMK Kesehatan Haji Sumatera Utara - Harahap, Syamsul Idris (JURNAL SOCIAL LIBRARY, 2021)
Basic life support is a set of interventions aimed at restoring and maintaining vital organ functions in victims of cardiac and respiratory arrest. The general purpose of this study was to determine the effect of basic life support health education on increasing knowledge of students at the Hajj Health Vocational School of North Sumatra in 2021. This type of research was a quantitative study with pre-experimental research methods according to the population in this study were 28. The sampling technique sample with total sampling, the number of samples as many as 28 people. The instrument used was a knowledge improvement questionnaire sheet. Data analysis was carried out with univariate and bivariate using the Wilcoxon test. The results of the study on the level of knowledge before basic life support health education was carried out: mean (63.21) and SD (10.308), while after being given basic life support health education: mean (81.43) and SD (13.119) so the difference in Mean – 18.22 . The results of the statistical test with the Wilcoxon test showed that there was an effect of basic life support health education on increasing the knowledge of students at SMK Kesehatan Haji North Sumatra in 2021. with a P value of 0.000 (